A novel terbium–mercury compound: Preparation, structure, and properties. Issue 7 (July 2020) - Chen, Wen-Tong
Using a hydrothermal reaction, a novel4f –5d isonicotinic acid complex {[Tb2 (IA)6 (H2 O)4 ](Hg3 Cl7 )} n ( n HgCl4 )· n Cl·4 n H3 O (1, HIA = isonicotinic acid) was synthesized and it was characterized by single crystal X-ray diffraction technique. Compound1 is characterized by a two-dimensional layer-like structure. The photoluminescence measurement using solid-state samples uncovered that it shows four emission peaks at 489, 546, 587, and 622 nm, of which the peak at 546 nm is the strongest. These peaks could be assigned to the 5 D 4 → 7 F 6, 5 D 4 → 7 F 5, 5 D 4 → 7 F 4, and 5 D 4 → 7 F 3 transitions of the Tb 3+ ions, respectively. The energy transfer mechanism of the photoluminescence emission was described by means of the energy level scheme of the Tb 3+ ions and the isonicotinic acid ligand. Compound1 shows remarkable CIE (Commission Internationale de I'Éclairage) chromaticity coordinates of (0.3633, 0.5038) in the yellowish green region. Compound1 possesses a wide semiconductor band gap of 2.97 eV, as unveiled by the solid-state UV-Vis diffuse reflectance experiment.